Lexical Access Speed and the Development of Phonological Recoding during Immediate Serial Recall. Issue 5 (20th October 2022) - AuBuchon, Angela M.; Elliott, Emily M.; Morey, Candice C.; Jarrold, Christopher; Cowan, Nelson; Adams, Eryn J.; Attwood, Meg; Bayram, Büsra; Blakstvedt, Taran Y.; Büttner, Gerhard; Castelain, Thomas; Cave, Shari; et al.
ABSTRACT: A recent Registered Replication Report (RRR) of the development of verbal rehearsal during serial recall revealed that children verbalized at younger ages than previously thought, but did not identify sources of individual differences. Here, we use mediation analysis to reanalyze data from the 934 children ranging from 5 to 10 years old from the RRR for that purpose. From ages 5 to 7, the time taken for a child to label pictures (i.e. isolated naming speed) predicted the child's spontaneous use of labels during a visually presented serial reconstruction task, despite no need for spoken responses. For 6- and 7-year-olds, isolated naming speed also predicted recall. The degree to which verbalization mediated the relation between isolated naming speed and recall changed across development. All relations dissipated by age 10. The same general pattern was observed in an exploratory analysis of delayed recall for which greater demands are placed on rehearsal for item maintenance. Overall, our findings suggest that spontaneous phonological recoding during a standard short-term memory task emerges around age 5, increases in efficiency during the early elementary school years, and is sufficiently automatic by age 10 to support immediate serial recall in most children. Moreover, the findings highlight the need to distinguish between phonological recoding and rehearsal in developmental studies of short-term memory.